The Role of Cardiolipin as a Scaffold Mitochondrial Phospholipid in Autophagosome Formation: In Vitro Evidence - Valeria Manganelli; Antonella Capozzi; Serena Recalchi; Gloria Riitano; Vincenzo Mattei; Agostina Longo; Roberta Misasi; Tina Garofalo; Maurizio Sorice (Biomolecules, 2021)
Cardiolipin (CL) is a hallmark phospholipid localized within the inner mitochondrial membrane. Upon several mitochondrial stress conditions, CL is translocated to specialized platforms, where it may play a role in signaling events to promote mitophagy and apoptosis. Recent studies characterized the molecular composition of MAM-associated lipid microdomains and their implications in regulating the autophagic process. In this study we analyzed the presence of CL within MAMs following autophagic stimulus and the possible implication of raft-like microdomains enriched in CL as a signaling platform in autophagosome formation. Human 2FTGH fibroblasts and SKNB-E-2 cells were stimulated under nutrient deprivation with HBSS. MAM fraction was obtained by an ultracentrifugation procedure and analyzed by HPTLC immunostaining. CL interactions with mitofusin2 (MFN2), calnexin (CANX) and AMBRA1 were analyzed by scanning confocal microscopy and coimmunoprecipitation. The analysis revealed that CL accumulates in MAMs fractions following autophagic stimulus, where it interacts with MFN2 and CANX. It associates with AMBRA1, which in turn interacts with BECN1 and WIPI1. This study demonstrates that CL is present in MAM fractions following autophagy triggering and interacts with the multimolecular complex (AMBRA1/BECN1/WIPI1) involved in autophagosome formation. It may have both structural and functional implications in the pathophysiology of neurodegenerative disease(s).